2020
DOI: 10.1111/ejn.15029
|View full text |Cite
|
Sign up to set email alerts
|

The effect of regular rhythm on the perception of linguistic and non‐linguistic auditory input

Abstract: The perceptual system does not process continuous sensory input equally at all times: some elements of the input are more attended than others (Landau & Fries, 2012). Attention samples the continuously changing environment in discrete chunks, which correspond to the periods of neural oscillations in the 4-8 Hz frequency band (VanRullen, 2018). Perception thus operates on these chunks of sensory information, while the phase of neural oscillations modulates attentional intensity, and thus the probability of perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…Our findings are consistent with recent evidence suggesting that the nature of sustained attention in humans and non-human primates is rhythmic and depends causally on endogenously generated neuronal oscillations that manifest in the EEG as θ (3-8 Hz) (Busch et al, 2009;Chakravarthi and VanRullen, 2012;Fiebelkorn et al, 2013Fiebelkorn et al, , 2018Dugué et al, 2015;McLelland et al, 2016;Helfrich et al, 2018) or α band (8-14 Hz) activity (Callaway, 1962;Busch and VanRullen, 2010;Drewes and VanRullen, 2011;Dugue et al, 2011;McLelland et al, 2016;Sherman et al, 2016). It contrasts, however, multiple recent works that failed to identify phase behavior relationships or showed inconclusive findings (Benwell et al, 2017;Ronconi et al, 2017;Rassili and Ordin, 2020;de Graaf and Duecker, 2021;Lin et al, 2021;Michail et al, 2021;Michel et al, 2021;Morrow and Samaha, 2021;Sheldon and Mathewson, 2021;Sun et al, 2021;van Es et al, 2021;London et al, 2022), even when the studies were replicating previous findings (Vigué-Guix et al, 2020;van der Werf et al, 2021).…”
Section: Discussionsupporting
confidence: 90%
“…Our findings are consistent with recent evidence suggesting that the nature of sustained attention in humans and non-human primates is rhythmic and depends causally on endogenously generated neuronal oscillations that manifest in the EEG as θ (3-8 Hz) (Busch et al, 2009;Chakravarthi and VanRullen, 2012;Fiebelkorn et al, 2013Fiebelkorn et al, , 2018Dugué et al, 2015;McLelland et al, 2016;Helfrich et al, 2018) or α band (8-14 Hz) activity (Callaway, 1962;Busch and VanRullen, 2010;Drewes and VanRullen, 2011;Dugue et al, 2011;McLelland et al, 2016;Sherman et al, 2016). It contrasts, however, multiple recent works that failed to identify phase behavior relationships or showed inconclusive findings (Benwell et al, 2017;Ronconi et al, 2017;Rassili and Ordin, 2020;de Graaf and Duecker, 2021;Lin et al, 2021;Michail et al, 2021;Michel et al, 2021;Morrow and Samaha, 2021;Sheldon and Mathewson, 2021;Sun et al, 2021;van Es et al, 2021;London et al, 2022), even when the studies were replicating previous findings (Vigué-Guix et al, 2020;van der Werf et al, 2021).…”
Section: Discussionsupporting
confidence: 90%
“…In another study, Barne et al (2021, this issue) presented rhythmically interleaved auditory and visual target stimuli and instructed participants to compare them to a probe after a brief retention interval. Although they did not find a behavioural benefit of rhythmic over non‐rhythmic stimulation (in line with de Graaf & Duecker, 2021; W. M. Lin, Oetringer, et al, 2021; Rassili & Ordin, 2020; Sun et al, 2021; all this issue), nor neural activity correlated with pre‐probe feature templates during the retention period, sensory cortices showed intermittent pre‐activation at the stimulus rhythm, likely in anticipation of processing the probe stimulus. This anticipatory anti‐phasic activation of auditory and visual cortices supports the idea of a periodic process that puts the sensory cortex into a maximally excitable state at the time of (potential) probe delivery.…”
Section: Can We Manipulate Brain Rhythms Through Rhythmic External St...mentioning
confidence: 68%
“…Rassili and Ordin (2020, this issue) compared whether presenting a regular sequence of (linguistic) syllables and (non‐linguistic) natural sounds similarly affected the detection of an intermediately presented target sound. They observed that neither type of stimuli showed an effect that exceeded target detection performance in a control condition with irregular stimulus presentation.…”
Section: Can We Manipulate Brain Rhythms Through Rhythmic External St...mentioning
confidence: 99%